0347 Possible pro-carcinogenic effect of endotoxin on lung cancer in an extended follow-up of Shanghai women textile workers. (23rd June 2014) - Checkoway, Harvey; Lundin, Jessica; Costello, Sadie; Ray, Roberta; Li, Wenjin; Eisen, Ellen; Astrakianakis, George; Seixas, Noah; Applebaum, Kate; Li Gao, Dao; Thomas, David
Abstract : Objectives: To examine further the association between endotoxin and risk of lung cancer among Shanghai women textile workers in an extended follow-up of the cohort. The initial follow-up indicated an inverse exposure-response relation. Method: We updated a case-cohort study nested within a cohort of 267 400 women. We compared exposure histories of 1456 incident lung cancers cases diagnosed during 1989–2006 with those of a reference subcohort of 3022 workers who were free of lung cancer at the end of follow-up. Endotoxin exposures were based on a quantitative job/exposure matrix. Relative risks (hazard ratios [HR]) associated with cumulative exposure, adjusted for age and smoking history, were estimated by Cox proportional hazards modelling adapted for the case-cohort design. We conducted exposure-response trend analyses for cumulative exposures lagged by 0, 10, and 20 years, and separately for time windows of <15 and >15 years since first exposure. Results: Overall, we observed no associations between cumulative exposure and lung cancer. In contrast, analyses by exposure time windows revealed a modestly elevated risk at the highest 3 exposure quintiles for exposures that occurred >15 years since first exposure; HR=1.28 (95% CI 0.90–1.82), HR=1.27 (95% CI 0.93–1.73), and HR=1.27 (95% CI 0.91–1.77), respectively; p-trend = 0.13. Conclusions: Exposures to endotoxin with long-term, relatively intense exposures were at most weakly associated with lung cancer risk in this cohort. The findings do not support a protective effect of endotoxin, but are suggestive of possible lung cancer promotion with increasing time since first exposure.